Novedades Para La Flora De La Argentina (Boletín de la Sociedad Argentina de Botánica, 2016)
Novelties for the Flora of Argentina. On the occasion of preparing the Flora of Cordoba, new records for the Argentinean flora have been registered as a result of intensive field trips and the revision of the main herbaria collections of the country. In this paper, three new records for the native flora and 17 for the introduced flora (casual aliens and naturalized species) of Argentina are presented. Descriptions, illustrations and a lectotypification are done. Furthermore, the presence of 10 introduced species is formally documented for the first time